2014
DOI: 10.1186/2193-1801-3-157
|View full text |Cite
|
Sign up to set email alerts
|

Simulated global change: contrasting short and medium term growth and reproductive responses of a common alpine/Arctic cushion plant to experimental warming and nutrient enhancement

Abstract: Cushion plants are important components of alpine and Arctic plant communities around the world. They fulfill important roles as facilitators, nurse plants and foundation species across trophic levels for vascular plants, arthropods and soil microorganisms, the importance of these functions increasing with the relative severity of the environment. Here we report results from one of the few experimental studies simulating global change impacts on cushion plants; a factorial experiment with warming and nutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…The increase in temperature is predicted to persist in the future, with warming continuing to develop fastest in the polar regions 3 . And this may affect vegetative growth, reproduction and phenology of plant in severe environments 18 19 20 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in temperature is predicted to persist in the future, with warming continuing to develop fastest in the polar regions 3 . And this may affect vegetative growth, reproduction and phenology of plant in severe environments 18 19 20 .…”
mentioning
confidence: 99%
“…As a result, short and medium term experiments indicate that global change may cause shifts in the hierarchical structure of plant communities 30 . There is also temporal variation in responses, as shrubs, cushion plants, and whole communities for instance, have shown differing short- and longer-term effects of nutrient addition 20 26 30 , whereas total communities may show contrasting responses to warming 31 . Finally, the initial conditions of the communities may determine response to global change, as well as biotic interactions 32 .…”
mentioning
confidence: 99%
“…It is not clear what ecological factors may limit the distribution of S. acaulis , especially in northern areas. Alatalo and Little (2014) showed experimentally that S. acaulis is sensitive to nutrient levels, with declining cover under longer‐term increased nutrient levels. Atmospheric humidity and substrate type have been suggested as limiting factors for S. acaulis in parts of Britain (Jones and Richards, 1962).…”
Section: Discussionmentioning
confidence: 99%
“…Another important functional group is cushion plants, which have great influence on ecosystems in polar and high alpine areas throughout the world as they often function as facilitator species across trophic levels (Cavieres & Arroyo 2002;Molenda, Reid & Lortie 2012;Roy et al 2013). Unfortunately, there are very few experimental studies on climate change impact on cushion plants, but the few that exist have shown contrasting responses to warming (Day et al 2009;Alatalo & Little 2014). The Reviewing Manuscript ability of functional groups to compete for light, nutrients, and other resources varies, and the responses may depend on interactions with co-inhabiting species; for instance, the most abundant ("dominant") species or functional group in a community can have a strong influences on the biotic conditions of the other species by either negative, competitive interactions or by positive, facilitative interactions (Grime 1998;Klanderud & Totland 2004).…”
Section: Introductionmentioning
confidence: 99%